PEMANFAATAN HASIL FERMENTASI LIMBAH CAIR TEH HIJAUPADA FREKUENSI PENYIRAMAN YANG BERBEDA TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Mull. Arg) - Retno Muningsih; Farhan Wardhana Majing (Jurnal Agrotek Lestari, 2020)
The experiment was conducted at Greenhouse and experimental garden of Polytechnic LPP Yogyakarta in Wedomartani from March to June 2016. This study aims to know the difference of frequency influence of watering liquid green tea fermentation on the initial growth of rubber plant seedlings. This research use non factorial Random Complete Block Design (RCBD) method, that is fermentation of liquid waste of green tea with 10 ml / polybag dosage with 3 treatments. The treatment given was control (P0), watering 2 weeks (P2), watering 4 weeks (P4). The giving of liquid organic fertilizer from waste liquid fermented green tea can enhance plant growth include rubber, i.e. plant height, number of leaves, green leaves, heavy wet and dry long & root plant rubber. At the 2 week watering frequency treatments showed the best results than the control treatment and the frequency of watering once every 4 weeks. Keywords: fermentation, tea liquid waste, liquid organic fertilize